Prevalence and distribution of chilli anthracnose incited by Colletotrichum capsici in southern Rajasthan - Shreesha Mishra; Amit Trivedi; R. K. Fagodiya; Pokhar Rawal; N. L. Meena (Annals of Agricultural Research, 2024)
Chilli is one of the most important spices and vegetable crop in India and the fourth major crop cultivated globally. Anthracnose disease is one of the major economic constraints to chilli production worldwide, espe cially in tropical and subtropical regions. To understand the prevalence and distribution pattern of chilli anthracnose disease was carried out in 25 villages of five major chilli growing districts viz. Udaipur, Banswara, Chittorgarh, Rajsamand and Dungarpur of southern Rajasthan during 2022. The pathogen associated with chilli anthracnose disease a survey was isolated and identified as Colletotrichum capsici. The study revealed that the disease had more occurrences in those districts where chilli is mainly grown. The maximum percent disease index was depicted in Vallabhnagar tehsil of Udaipur district (28.55%) followed by Kapasan tehsil of Chittorgarh (26.43%). Minimum PDI was recorded in Nathdwara Tehsil of Rajasamnd (21.78%). This disease was found to cause severe losses on a wider area under chilli cultivation in Rajasthan as well as India.